Lidocaine for Status Epilepticus in Pediatrics. (25th August 2015) - Zeiler, Frederick A.; Zeiler, Kaitlin J.; Teitelbaum, Jeanne; Gillman, Lawrence M.; West, Michael; Kazina, Colin J.
Abstract: Background: Our goal was to perform a systematic review of the literature on the use of intravenous lidocaine in pediatrics for status epilepticus (SE) and refractory status epilepticus (RSE) to determine its impact on seizure control. Methods: All articles from MEDLINE, BIOSIS, EMBASE, Global Health, HealthStar, Scopus, Cochrane Library, the International Clinical Trials Registry Platform (inception to November 2014), and gray literature were searched. The strength of evidence was adjudicated using both the Oxford and Grading of Recommendations Assessment, Development, and Evaluation methodologies by two independent reviewers. Results: Overall, 20 original studies were identified, with 19 manuscripts and one meeting abstract. Two hundred and thirty-five pediatric patients were treated for 252 episodes of SE/RSE. Patients had varying numbers of antiepileptic drugs (two to eight) on board before lidocaine therapy. During 20 of the 252 (7.9%) episodes of SE/RSE, phenytoin was on board. The dose regimen of lidocaine varied, with some using bolus dosing alone; others used a combination of bolus and infusion therapy. Overall, 60.0% of seizures responded to lidocaine, with complete cessation and greater than 50% reduction seen in 57.6% and 12.3%, respectively. Patient outcomes were sparingly reported. Conclusions: There currently exists Oxford level 2b, Grading of Recommendations Assessment Developement, and Evaluation C evidence to support the consideration of lidocaine for SE and RSE in the pediatric population. Further prospective studies of lidocaine administration in this setting are warranted. RÉSUMÉ: Traitement de l'état de mal épileptique par la lidocaïne en pédiatrie. Contexte : Nous avons effectué une revue systématique de la littérature à propos de l'utilisation de la lidocaïne par voie intraveineuse chez des enfants en état de mal épileptique (ÉMÉ) ou d'ÉMÉ résistant au traitement (ÉMÉR) afin de déterminer son impact sur le contrôle de l'ÉMÉ. Méthode : Nous avons recherché tous les articles sur ce sujet indexés dans MEDLINE, BIOSIS, EMBASE, Global Health, HealthStar, Scopus, Cochrane Library, the International Clinical Trials Registry Platform (du début jusqu' à novembre 2014) ainsi que la documentation parallèle. Deux réviseurs indépendants ont utilisé l'Oxford and Grading of Recommendations Assessment, Development and Evaluation pour évaluer la qualité des études. Résultats : En tout, 20 études originales ont été identifiées, dont 19 manuscrits et un résumé. Deux cent trente-cinq patients d'âge pédiatrique ont ainsi été traités au cours de 252 épisodes d'ÉMÉ/ÉMÉR. Les patients recevaient plusieurs médicaments antiépileptiques (de 2 à 8) avant le traitement par la lidocaïne. Au cours de 20 des 252 épisodes d'ÉMÉ/ÉMÉR (7, 9%), le patient recevait de la phénytoïne. La dose de lidocaïne était variable : certains ont reçu seulement un bolus alors que d'autres ont reçu la lidocaïne en bolus et en perfusion. En tout, 60% des crises ont répondu à la lidocaïne avec arrêt complet de la crise chez 57, 6% des patients et plus de 50% de réduction chez 12, 3% des patients. Peu d'information était rapportée sur l'issue chez les patients. Conclusions : Il y a actuellement des données de niveau 2b, selon le Grading of Recommendations Assessment, Development and Evaluation C, à l'appui de l'utilisation de la lidocaïne pour traiter l'ÉMÉ et l'ÉMÉR chez les patients d'âge pédiatrique. Il serait donc justifié de procéder à des études prospectives sur l'utilisation de la lidocaïne dans ce contexte.